A combined technique using phase change material and jet impingement heat transfer for the exhaust heat recovery applications – A numerical approach. (15th November 2022) - Bharanitharan, K.J.; Kang, Shung-Wen; Sanjay, K.J.; Senthilkumar, S.
Abstract: Increasing the development of industries and automobiles requires developing a new system to recover exhaust heat emitted from these sources. Phase change materials are known for energy storage because of their latent heat properties. With this idea, a combined technique of phase change material (PCM) and jet impingement heat transfer is proposed where the exhaust gas acts as an impinging jet on storage with phase change material. The study is performed numerically with ANSYS Fluent. Initially, the study involves validating numerical setup for melting of PCM and Jet impingement heat transfer with benchmark experimental data. Later, both models are combined to study exhaust heat recovery. Parametric studies are performed by changing the materials, temperature, Reynolds number, spacing ratio (ratio of the height of the exhaust inlet from the impinging plate to the diameter of inlet), and orientation of the system. The parametric study reveals several important characteristics to be considered while choosing the material, such as conductivity and latent heat. The temperature study shows that the significance of the Reynolds number is reduced as the temperature is increased. By changing the spacing ratio from 2 to 6, the energy recovery is decreased by 23 %. However, changing the orientations of the system has shown a significant improvement on the energy recovery. Graphical abstract: Unlabelled Image Highlights: A combined technique using phase change material (PCM) and jet impingement heat transfer is envisaged numerically for exhaust heat recovery applications. Parametric studies are performed with three different PCM materials such as Liquid Gallium, Lauric acid and n-Octadecane, operating temperature, spacing ratio, Reynolds number and orientation of the geometry. Increasing the temperature (from 200 ° C to 600 ° C) and the Reynolds number have shown a significant improvement in both energy recovery and melt fraction for all the three chosen PCM materials. Increasing the distance between the exhaust jet inlet and the impinging plate for the same material has shown an adverse effect on melting and energy recovery rate. Changing the geometrical orientation from horizontal to vertical improves the energy recovery by 30 %.